2022
DOI: 10.3390/nu14224941
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Dietary Behavior, and Body Weight Changes during the COVID-19 Nationwide Level 3 Alert in Taiwan: Results of a Taiwanese Online Survey

Abstract: This cross-sectional study aimed to explore the influence of the COVID-19 pandemic on physical activity (PA) and dietary habits, and their impact on body weight changes during the Level 3 alert period that resulted in the lockdown in Taiwan. The study was conducted between 1 July 2021 and 15 July 2021, using a Google Forms online survey platform. Personal data, anthropometric information, PA information, and dietary habit information were collected before and during the alert period. Exactly 374 respondents, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…On the other hand, some studies also found that increased fear and stress during the COVID-19 pandemic might be associated with adverse lifestyle change [ 8 , 39 ]. According to a previous study to investigate lifestyle changes during the COVID-19 Lv3 alert in the Taiwan general population, the online survey showed a significant decrease in physical activity but no significant changes in body weight during this period [ 44 ]. Notably, it has been reported that an increasing trend in obesity across more than a decade based on the data from Nutrition and Health survey in Taiwan [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies also found that increased fear and stress during the COVID-19 pandemic might be associated with adverse lifestyle change [ 8 , 39 ]. According to a previous study to investigate lifestyle changes during the COVID-19 Lv3 alert in the Taiwan general population, the online survey showed a significant decrease in physical activity but no significant changes in body weight during this period [ 44 ]. Notably, it has been reported that an increasing trend in obesity across more than a decade based on the data from Nutrition and Health survey in Taiwan [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that contrasting findings were reported in other studies, where notable changes in bodyweight were not observed in people with diabetes. [17][18][19] This report presents the first comprehensive analysis of COVID-19's impact on glycemic, weight, and blood pressure control in a large patient population in Malaysia, aiming to fill knowledge gaps and provide insights for targeted interventions and management strategies. Nevertheless, our study had some limitations.…”
mentioning
confidence: 99%
“…In this Special Issue, two contributions linked to COVID-19 were presented. Ke et al [9] presented a study that described an online survey result of PA, dietary behavior, and body weight changes during the COVID-19 nationwide lockdown in Taiwan. The results were obtained from the replies of 374 respondents, aged between 20 and 66, and showed a negative impact on all PA levels of participants, with a significant increase in a sedentary lifestyle.…”
mentioning
confidence: 99%